Teacher as a Motivator: Gender, Ownership of Educator Certificates, and Age of Elementary Teachers in Improving Student Motivation during Online Learning - Juliartawan, I Gusti Ngurah Kade Angga; Nanci Riastini, Putu (Universitas Pendidikan Ganesha, 2022)
The online learning process during the Covid-19 pandemic tends to be more difficult and makes the students' motivation in elementary school low. Elementary school teachers have an important role in increasing and maintaining student motivation during the online learning process. This study aims to describe the role of teachers in terms of gender, ownership of educator certificates, and teacherage in increasing student motivation during online learning. The method used in this research is a descriptive method with quantitative data analysis techniques. Respondents in this study were elementary school teachers, as many as 11 people. Determination of the sample using a saturated sampling technique. The data collection method in this study was a questionnaire. The questionnaire consisted of 15 questions referring to 5 aspects of the teacher as a motivator. There are differences in the teacher's role as a motivator regarding gender, ownership of educator certificates, and teacherage. The results showed that elementary school teachers had tried to motivate students during online learning with a good dominant score. Unfortunately, some aspects are still in enough category, namely the indicators of giving reward-punishment, elements of the variation of the learning process, and aspects of using technology. The results also show that female teachers are better than male teachers, non-certified teachers are better than certified educators, and young teachers are better than older teachers.